Forgery detected [electronic resource] : by which is evinced how groundless are all the calumnies cast upon the editor, in a pamphlet published under the name of Arthur Dobbs, Esq. - Middleton, Christopher, d. 1770; Dobbs, Arthur, 1689-1765. Remarks upon Capt. Middleton's defence. (London : Printed for M. Cooper . and G. Brett ., 1745)
Electronic reproduction. Mode of access: Internet. 44